Bellman Type Inequality for Sugeno Integrals - Bayaz Daraby; Ramin Mosalman (Sahand Communications in Mathematical Analysis)
In this paper, we prove  Bellman type inequality for Sugeno integral and generalize it for pseudo-integrals. Furthermore, we generalize the Bellman's inequality in abstract spaces. The strengthened version of this inequality is demonstrated in pseudo-integrals and abstract spaces. Also, we illustrate theorems with some examples.